Pengaruh Manajemen Perkantoran Dalam Meningkatkan Prestasi Siswa Madrasah Tsanawiyah Swasta Ex PGA Proyek Univa Medan - Pasaribu, Gusti Aprila; Alfa, Luhfiah Malaya; Juliani, Duwi; Pane, Riswanda Pratama; Darmansyah, Tengku (Yayasan Daarul Huda Kruengmane, 2024)
The research was conducted on Jl. SM Raja, Km. 5, 5, Harjosari 1 Village, Medan Amplas District. The aim is to describe the influence of office management in improving student achievement at the private Tsanawiyah Madrasah Ex PGA Univa Medan Project. By conducting interviews with the Deputy Head of the Madrasah, especially in the field of Student Affairs. The aim of this research is to find out how influential office management is in increasing student achievement at the private Tsanawiyah Madrasah Ex PGA Univa Medan Project. By carrying out extracurricular program activities or holding competitions with the involvement of students. And likewise, observations and interviews were carried out on each individual to find out the influence of office management in improving student achievement at the private Tsanawiyah Madrasah Ex PGA Univa Medan Project. This interview was addressed to several teachers, deputy principals of the Madrasah and several students at this madrasah.. Data This is presented and processed and presented using analytical methods. This research shows that all activities held in each Madrasah are improving, coordinating, directing and shaping the Madrasah in a better direction, in order to create a more advanced Madrasah